Functional Outcome of Carpal Tunnel Syndrome After Exercise versus Ultrasound Diathermy - Irma Ruslina Defi; Marina Annette Moeliono; Widjaja Laksmi Kusumaningsih (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objective: to compare the effectiveness of Tendon and Nerve Gliding Technique (TNGT) exercise with ultrasound diathermy.Methods: Twenty Carpal Tunnel Syndrome (CTS) hands meet the inclusion criteria and divided into2 groups: TNGT exercise and Ultrasound group. The subjects’ characteristics in the two groups are homogenous.Results: The statistical analysis results using Friedman test on pain/paresthesia complaint and hand functional status in each group is significant. Using the ANOVA, results of pain/paresthesia complaintbetween two groups shows a significant difference in the 4th measurement and results of functional status between two groups show a significant difference in the 9th measurement.Conclusions: Our study emphasized the TNGT exercise combined with splinting will be a good alternative treatment for CTS beside ultrasound diathermy combined with splinting, since TNGTexercise group has the same effectiveness with ultrasound diathermy group in decreasing VAS and has better effectiveness in improvement of FSS.Keywords: CTS, TNGT, Ultrasound Diathermy, VAS, FSS.